Potensi dan Performa Reproduksi Indukan Sapi Bali dalam Mendukung Usaha Pembiakan di Stasiun Lapang Sekolah Peternakan Rakyat - Sari, D. A. P.; Muladno; Said, S. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Reproductive performance of female cattle is one of the important factors that need to be known in supporting the efficiency of beef cattle breeding programs so that the dam can produce calves every year. This study aimed to evaluate the potential and reproductive performance of female Bali cattle to preparing a baseline for cattle breeding production in SL-SPR Maju Bersama, Sungai Lilin District. Three hundred and thirty female Bali cattle owned by 247 farmers were measured and recorded based on their production and reproduction performance. Data were collected by interview and observation. Data were analyzed using statistical and descriptive methods. Reproductive performance obtained is the age first calving 1098±120 days; calving interval 457,25±8,75 days; days open 109,25±8,57 days and service per conception 5,46±0,42. The average female cattle have a BCS value of 3 (43%). The result showed that the breeding of Bali cattle at SL-SPR had sufficient potential, but it was necessary to improve performance. The basic data obtained can be used to start a breeding business to increase populations and improve the genetic quality of Bali cattle.